The Gambia at Crossroads: Presidential Pardon a Constitutional Fiat - Mendy, Ousu (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
The Constitution of the Republic of The Gambia, 1997 is promulgated with the original intent to be a living constitution with clauses that permit amendments. While a constitution is a legal and political document agreed upon by stakeholders as the principal instrument in governing the affairs of a state, it is a liability in the context of its dependency on what the people want it to ‘do’ and therefore, convictions based on cogent evidence need to be made from a different squint. Politization of the living nature of a constitution joint with partisan politics and the resolute nature of the political class in securing their ‘throne’ in democracy expresses the ideology and praxis of presidential pardon as a bait to attract masses to their camps. This research proposes for revisitation of Section 82 of the Constitution in the aftermath of the proclivity of the government to enforce it, notwithstanding the crimes inmates were convicted of. In this research, doctrinal legal research is used and finally concludes that Section 82 is not a constitutional fiat and thus, its application must be guided principally by constitutional ethos and mores in guaranteeing justice through respect and protection of the rights of the people.